(untitled) (Proceedings of the International Conference on Education, 2025)
Genetics is a rapidly growing branch of biology, playing a crucial role across various disciplines, emphasizing the importance of genetic literacy for students. Like other forms of literacy, genetic literacy has emerged as a societal trend, highlighting the need for a foundational understanding of genetics among academics and the general public. However, students often perceive genetics as challenging due to its abstract molecular concepts, making effective teaching strategies essential. This study employed content analysis to analyze articles from Indonesian biology education journals indexed by SINTA from 2013 to 2024, focusing on efforts to enhance the quality and effectiveness of genetics instruction. The analysis reveals a general increase in publication numbers each year, with slight declines in 2017 and 2020. The most common research designs were R&D studies, which produced educational tools such as media, modules, and other instructional resources. Genetic materials, especially at the high school level, were the most frequently researched topic, as they provide essential foundational concepts for understanding biology. Descriptive analysis (percentage) was the most prevalent data analysis method, although it could have been more effective in generalizing findings. Digital media applications emerged as the most popular teaching strategy, reflecting the complexity of genetics, which benefits from visible aids. Recommendations for future research include employing more precise data analysis techniques and further exploration using qualitative or mixed-method approaches for a more comprehensive understanding of genetics instruction.